Concussion incidence and recovery of neurocognitive dysfunction among youth athletes taking antibiotics: A preliminary, multicenter retrospective cohort study - Asghar, N.; Ali, M.; Hannah, T.; Li, A. Y.; Asfaw, Z.; Hrabarchuk, E. I.; Quinones, A.; McCarthy, L.; Vasan, V.; Murtaza-Ali, M.; Lin, A.; Alasadi, H.; et al. (International Journal of Athletic Therapy & Training, 2023)
Concussions are the leading cause of injury among youth athletes, and antibiotics are the most prescribed pediatric medication in the United States. Antibiotics have shown to exert neuroprotective effects in animal models of traumatic brain injury, but to date, no human studies exist. Between 2009 and 2019, 6,343 adolescent athletes with differential antibiotic use at baseline were administered Immediate Post-concussion Assessment and Cognitive Testing at baseline and twice postinjury. Chronic antibiotic use was associated with a reduced risk for concussion (odds ratio 0.54), increased postconcussive symptomology and neurocognitive burden, and improved recovery by follow-up, a median of 7 days after concussion. This preliminary retrospective analysis suggests antibiotic use may impart neuroprotection up to a certain severity threshold, leading to fewer, yet more severe concussions that tend to recover faster.